Analysis of the Application of Disciplinary Penalties Against Police Members Who Perform Siri Marriage in the Legal Area of Rokan Hilir Police Station - Pratama Sitepu, Edi; Risdalina, Risdalina; Kumalasari Munthe, Indra (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
This research aims to find out about the Analysis of the Application of Disciplinary Penalties Against Police Members Who Perform Siri Marriage in the Rokan Hilir Police District. This research uses Normative-empirical legal methods, namely through a qualitative approach. The data in this study uses secondary data (literature review). The discussion results in the application of disciplinary penalties against members of the Indonesian National Police who commit Siri marriage in the Rokan Hilir Police Legal Area by Government Regulation (PP) No. 2 of 2003 concerning Disciplinary Regulations for Members of the Indonesian National Police. By Article 1 number 5, disciplinary actions that are constructive are imposed directly on members of the Indonesian National Police." number 6 states: Disciplinary punishment is imposed by superiors who have the right to punish members of the Indonesian National Police through a Disciplinary Hearing." further Article 13 Discipline violators can be dishonourably discharged if they repeat the offence within the time of assignment to the same unit. So, violators will get punishment in the form of dishonourable dismissal if members of the National Police commit the same offence at the time of assignment and in the same unit. The implication of this research is the importance of maintaining discipline in the police institution, including enforcing rules related to Siri marriage to ensure good police performance and image in the eyes of the community.